2005
DOI: 10.1155/2005/716873
|View full text |Cite
|
Sign up to set email alerts
|

Cardiobacterium hominis Endocarditis: A Case Report and Review of the Literature

Abstract: The present case report describes the clinical course of a patient who presented with Cardiobacterium hominis endocarditis. A review of the literature follows the case presentation. C hominis, a fastidious Gram-negative bacillus, is a member of the HACEK group of microorganisms (Haemophilus species, Actinobacillus actinomycetemcomitans, C hominis, Eikenella corrodens and Kingella kingae). Endocarditis caused by C hominis is uncommon and generally follows a subacute course. Patients may present with constitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…6,7 Because HACEK microorganisms are part of the normal oral flora, recent dental procedures are a risk factor for developing endocarditis with this group of microorganisms - especially for patients with underlying heart disease. Wormser et al .…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Because HACEK microorganisms are part of the normal oral flora, recent dental procedures are a risk factor for developing endocarditis with this group of microorganisms - especially for patients with underlying heart disease. Wormser et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiobacterium hominis, is a member of the HACEK group of organisms associated with culture negative endocarditis. These organisms account for approximately 3-6% of cases of SBE diagnosed in North America 1,2 . C hominis is a constituent of the human oral cavity and upper respiratory tract normal flora 2,3 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that long incubation times of at least five to seven days were required to culture C. hominis; however, recently published cases and reviews have demonstrated consistent growth within five days. 5 Similarly, a review of laboratory incubations showed that all cases of HACEK IE were diagnosed within 5 days, and all incubations beyond 5 days yielded no growth. 6 This is important given the ever-increasing demands on microbiology labs and the extra costs incurred from prolonged incubation with no evident benefit.…”
Section: Smentioning
confidence: 98%
“…However, in contrast to the Gram-positive bacteria commonly causing IE, intravenous drug use does not seem to be a risk factor for C. hominis IE likely due to its absence on the skin at points of vascular injury. 5 Dental manipulation has been classically associated with the development of transient bacteremia even in immunocompetent hosts. 10 More recently, even mild dental manipulation from brushing has been shown to cause transient bacteremia.…”
Section: Risk Factors For C Hominis Iementioning
confidence: 99%